2007
DOI: 10.1161/atvbaha.106.132266
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Phosphate Transport in Rat Vascular Smooth Muscle Cells

Abstract: Objective-Hyperphosphatemia and inorganic phosphate (Pi) transport by vascular smooth muscle cells (VSMCs) have been implicated in the pathogenesis of vascular calcification. The aim of this work has been to characterize Pi transport in VSMCs. Methods and Results-Primary cultures of VSMCs express both high affinity Na-dependent and Na-independent components of Pi transport. Under physiological conditions both transport systems are saturated, show similar activity, and are inhibited by increasing pH. The Na-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
139
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(158 citation statements)
references
References 33 publications
17
139
2
Order By: Relevance
“…In an attempt to dissect possible mechanisms for insulin effect on calcification, we found that insulin induces phosphate transport into VSMC. Recently, the kinetic and molecular characteristics of phosphate transport in VSMC have been analyzed in detail, showing that Na-dependent uptake relies exclusively on type III sodium-dependent phosphate co-transporters Pit-1 and Pit-2 (21). Here, we have demonstrated that this is due to an increase in capacity but not affinity for phosphate transport, and may be explained mainly by insulin induction of Pit-2, and to a lesser extent Pit-1.…”
Section: Discussionmentioning
confidence: 54%
“…In an attempt to dissect possible mechanisms for insulin effect on calcification, we found that insulin induces phosphate transport into VSMC. Recently, the kinetic and molecular characteristics of phosphate transport in VSMC have been analyzed in detail, showing that Na-dependent uptake relies exclusively on type III sodium-dependent phosphate co-transporters Pit-1 and Pit-2 (21). Here, we have demonstrated that this is due to an increase in capacity but not affinity for phosphate transport, and may be explained mainly by insulin induction of Pit-2, and to a lesser extent Pit-1.…”
Section: Discussionmentioning
confidence: 54%
“…[3][4]7 NaPi-3 proteins (Pit1 and Pit2) are broadly expressed and believed to play housekeeping as well as pathologic roles in different cells. 70 -73 Extracellular Pi stimulates calcification in VSMC through inorganic Pi influx by NaPi-3 [73][74][75] and cell- surface Pit2 reorganization. 73,76 High ambient Pi accelerates mineralization 44,49 and stimulates surrogate markers of osteogenesis in VSMC, 49,77 spawning the hypothesis that high Pi stimulates "ossification" of VMSC.…”
Section: Pathogenic Role Of Klotho In Progression Of Ckd and Its Compmentioning
confidence: 99%
“…A number of studies demonstrate a role for PiT1 in osteoblast-and chondrocyte-mediated mineralization (95)(96)(97). PiT1 expressed on matrix vesicles derived from the parent cell provides phosphate needed for mineralization.…”
Section: Pit1mentioning
confidence: 99%